2000
DOI: 10.4049/jimmunol.164.6.3368
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine Is an Epithelial and Endothelial Cell-Derived Chemoattractant for Intraepithelial Lymphocytes in the Small Intestinal Mucosa

Abstract: Fractalkine is a unique chemokine that combines properties of both chemoattractants and adhesion molecules. Fractalkine mRNA expression has been observed in the intestine. However, the role of fractalkine in the healthy intestine and during inflammatory mucosal responses is not known. Studies were undertaken to determine the expression and function of fractalkine and the fractalkine receptor CX3CR1 in the human small intestinal mucosa. We identified intestinal epithelial cells as a novel source of fractalkine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
133
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(145 citation statements)
references
References 53 publications
(54 reference statements)
9
133
0
1
Order By: Relevance
“…Unexpectedly, we found that transmembrane CX 3 CL1 was expressed predominantly on the apical surface of RTEC. This pattern of expression mirrors that found in epithelial cells of biliary ductules (44) but differs markedly from that of intestinal epithelial cells, where CX 3 CL1 largely is expressed in the basolateral membrane and in regions of intercellular contact (45,46). In the intestine, as in the kidney, expression of CX 3 CL1 is highly enhanced in disease states that are marked by active inflammation (14,45,47).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Unexpectedly, we found that transmembrane CX 3 CL1 was expressed predominantly on the apical surface of RTEC. This pattern of expression mirrors that found in epithelial cells of biliary ductules (44) but differs markedly from that of intestinal epithelial cells, where CX 3 CL1 largely is expressed in the basolateral membrane and in regions of intercellular contact (45,46). In the intestine, as in the kidney, expression of CX 3 CL1 is highly enhanced in disease states that are marked by active inflammation (14,45,47).…”
Section: Discussionsupporting
confidence: 70%
“…CX 3 CL1 in intestinal epithelium has been shown to recruit leukocytes in inflammation and to regulate cell survival and wound repair (7,45,55). In intestinal epithelium, CX 3 CL1 is expressed predominantly on the basolateral surface, where it is in direct contact with CX 3 CR1-expressing host leukocytes, including macrophages, lymphocytes, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The full-length molecule can be cleaved from the cell membrane by tumor necrosis factor-a-converting enzyme, a member of the ADAM (disintegrin and metalloprotease) family, and ADAM10, to produce a soluble form that includes the chemokine domain and most of the stalk region. 15 CX 3 CL1 is expressed on the surface of endothelial cells, 17 epithelial cells, 17,18 DCs 19,20 and neurons 21 and is induced by pro-inflammatory cytokines, such as interleukin (IL)-1 and tumor necrosis factor-a. 22,23 The CX 3 CL1 receptor, CX 3 CR1, is capable of mediating both leukocyte migration and firm adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is known to be a potent chemoattractant for CD8 ϩ and CD4 ϩ T cells, natural killer cells, and monocytes expressing its receptor (CX3CR1), whereas the former promotes strong adhesion of these leukocytes in an integrin-independent manner. 6,7 Muehlhoefer et al 8 reported fractalkine protein and messenger RNA (mRNA) expression in epithelial cells and endothelial cells in small intestine under normal conditions, and their upregulation during inflammatory bowel disease. 8 They also disclosed that fractalkine expressed on the intestinal epithelium may regulate a subpopulation of CD8 ϩ T cells in the epithelial layer (intestinal intraepithelial lymphocytes [IELs]).…”
mentioning
confidence: 99%
“…6,7 Muehlhoefer et al 8 reported fractalkine protein and messenger RNA (mRNA) expression in epithelial cells and endothelial cells in small intestine under normal conditions, and their upregulation during inflammatory bowel disease. 8 They also disclosed that fractalkine expressed on the intestinal epithelium may regulate a subpopulation of CD8 ϩ T cells in the epithelial layer (intestinal intraepithelial lymphocytes [IELs]). 8 Biliary epithelial cells (BECs) are known as immunologically potent cells, and BECs of inflamed bile ducts actively participate in inflammation by secreting cytokines and expressing immune receptors.…”
mentioning
confidence: 99%